A survey of students participating in a computer-assisted education programme - Yel, Elif Binboğa; Korhan, Orhan (International Journal of Research in Education and Science, 2015)
This paper mainly examines anthropometric data, data regarding the habits, experiences and attitudes of the students about their tablet/laptop/desktop computer use, in addition to self-reported musculoskeletal discomfort levels and frequencies of students participating in a tablet-assisted interactive education programme. A two-part questionnaire was used to collect data. Results revealed that students are experiencing musculoskeletal discomforts highly at the neck, lower back and upper back regions.. The survey results are of critical importance because making reasonable recommendations to the new generations for healthy use of desktop/laptop/tablet computers is only possible if we can understand the relationships and risk factors involved in and eliminate the risks to prevent musculoskeletal discomfort. © 2015, International Journal of Research in Education and Science. All rights reserved.
Keywords: Desktop; Laptop; Musculoskeletal discomfort; Tablet